“Uma dor compartilhada”: análise da experiência de vulnerabilidade estendida no bem-estar dos familiares de pessoas com câncer - Sousa, Bruna Cordeiro de (2021)
Cancer presents itself as one of the diseases with the highest number of diagnoses in recent decades. Most of the difficulties faced by the individual affected by the disease originate from the vulnerability that emerges from this experience. It is argued in this paper that this experience of vulnerability also affects the family members of the person with the disease, who experience what the authors call shared vulnerability. Given the above, the objective of this paper is to understand how the experience of extended vulnerability occurs and how it affects the well-being of family members of people with cancer. To achieve this, a qualitative methodology was chosen, using the oral history technique for data collection. The conversations were conducted through a remote access platform and messaging application, since face-to-face meetings are temporarily impossible due to the social distance from the COVID-19 pandemic. Using the interpretive paradigm, the data were analyzed and structured according to Baker et al. (2007). From the speeches of the participants, it was possible to understand that the shared vulnerability of family members of people with cancer is characterized by the stigma rooted in the disease, the impotence felt by these people and the neglect of external actors, in addition to causing changes in the lives of these people and getting them to look for ways to deal with them. It was also found that this experience causes changes in the emotional and financial well-being of these people, changing their buying behavior and bringing lasting consequences in their lives. It is concluded, therefore, that having a cancer patient in the family generates a secondary vulnerability in the family, influencing their financial and emotional well-being, transforming their perceptions of the world and causing profound impacts on their lives. This work seeks to contribute to society while offering a direction for the creation of plans that can cover all the needs of these individuals, their wellbeing being a measure to be considered in the allocation of resources in public and private health services.